Microanatomy of the Skin of Prepuce in Golden Jackal (Canis aureus indicus) - Rajani, C.V. (Indian Journal of Veterinary Anatomy, 2020)
Golden jackal (Canis aureus) is the most wide-spread jackal species and is extensively found in India. The preputial glands produce pheromones which may play a major role in sexual behaviour. The glands exist as separate masses in rodents. The external layer of preputial skin was made up of keratinized stratified squamous epithelium and was similar to skin of other body regions. Non-keratinized stratified squamous epithelium lined the internal layer of prepuce. The dermis enclosed few compound hair follicles. Dermis also contained modified sebaceous glands, coiled apocrine and merocrine sweat glands. The modified sebaceous glands are the preputial glands and had a lobulated appearance. Acini of the gland resembled mucous secretary units and had eosinophilic,  pale, vacuolated, and foamy cytoplasm. The preputial gland secretion in golden jackal may play a role in sexual behaviour and in territory marking.